Preparation of Foreign Language Graduates to Teach English for Specific Purposes at the Academic Level - Patrycja Małgorzata Linkiewicz (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: Contemporarily it is not enough to be able to use English solely for general purposes. Thus, foreign language teachers have to obtain a great deal of competences, among which some researchers point to the skills and knowledge from the specialist field. Research aim: The objective of the article consists in analysing if foreign language teachers are sufficiently prepared to teach English for Specific Purposes (ESP) to students of higher education institutions. Evidence-based Facts: The graduates of philology are fully unprepared to teach ESP, while graduates of applied linguistics are partially prepared to undertake such tasks. The main problem with teaching ESP lies, however, in the lack of appropriate didactic materials. Thus, foreign language teachers are left with no other choice than to create their own materials, apply creative teaching methods (e.g. presentations prepared by the students), or to search for the materials loosely connected with a given discipline. Summary: The practical solutions to the problem depicted in the article are suggested, and they are as follows: incorporation of "specialist foreign language methodology" into academic curricula, organisation of courses from a specific field for foreign language teachers, researching the scale of the problem, mutual exchange of experience and materials between the teachers, improvement of the hitherto created coursebooks and materials with account taken of the communicative approach towards language learning, creation of specialist coursebooks.